Analysis of the management of choledocholithiasis and it’s outcome with the role of preoperative endoscopic retrograde cholangiopancreatography and magnetic resonance cholangiopancreatography - Valarmathi, M.; Andappan, Anandi (International Surgery Journal, 2019)
Background: Choledocholithiasis implies stones in the common bile duct (CBD). Most of the common bile duct stones are those that have passed into the bile duct from the gall bladder. About 20 to 25% of patients above the age of 60 with symptomatic gall stones are likely to have stones in the CBD. To analyse the role of ERCP and MRCP in the management of choledocholithiasis. Methods: About 60 patients who are attending the General Surgery OPD of Rajiv Gandhi Government General Hospital, Madras Medical College, Chennai, Tamil Nadu, India from the October 2017-March 2018 were included in the study with confirmed common bile duct stones with or without gall stones were chosen. patients were categorized into group A- who has undergone a successful ERCP followed by laparoscopic cholecystectomy and group B- who underwent open cholecystectomy with CBD exploration. Results: Ultrasonography was done in 57 patients, of which 41 patients showed CBD stones (71.93%), 12 patients showed dilated CBD in the presence of cholelithiasis (21.05%) and in the remaining 4 patients (7.01%) this investigation showed only cholelithiasis. Since clinical condition warranted, authors proceeded with further hepatobiliary imaging, which revealed choledocholithiasis. Conclusions: Magnetic resonance cholangio pancreatography can also be used for follow up of the patients with choledocholithiasis after therapy, to look for the presence of retained stones, since it can detect stones even in the size as small as 2 mm. Selective use of intraoperative choledochoscopy in suspected cases helps in reducing the incidence of retained stones.